Instability of some equatorially trapped waves. Issue 6 (10th June 2013) - Constantin, Adrian; Germain, Pierre
Abstract : [1] A high‐frequency asymptotics approach within the Lagrangian framework shows that some exact equatorially trapped three‐dimensional waves are linearly unstable when their steepness exceeds a specific threshold. Key Points: Instability investigation of some new waves. The instability mechanism differs from that for Kelvin waves. The Lagrangian flow is not explicitly available in the Eulerian representation.